Volume equations for estimating timber yield of Hevea brasiliensis Muell Arg in plantations of the stages of adulthood and old age - Gómez González, Juan Pablo; Domínguez-Domínguez, Marivel; Martínez-Zurimendi, Pablo; Ramírez Valverde, Gustavo (Instituto de Ecología, A.C., 2018)
It is necessary evaluate the use of rubber wood; to do that, an equation has been generated for estimating timber volumes through models for ages 25-51 years. A dasometric inventory was carried out in 11 plantations of rubber (Hevea brasiliensis Muell Arg.), established in Huimanguillo, Tabasco. Plantations are 25 to 51 years old, established planting of 570 trees per hectare; average diameter 31.35 cm; dominant average height 27.25 m; basal area 49.82 m² ha-1; commercial height 13.29 m; Pressler height 9.74; Pressler timber volume with bark 1.47 m3 tree-1; Reineke index 876. The volume equation was fitted considering the shape of the tree through the volume of Pressler, for bole volume standing. Berkhout volume models, Kopezky, Hohenadl-Krenn, Husch, Spurr, Stoate, Meyer, Schumacher and third-degree Polynomial were tested. Applying cross-validation, the Kopezky model presented the best coefficient of determination with high reliability. This model can be used to estimate volume of trees, to generate volume mensuration rate and to evaluate the productive potential of this specie for use in Tabasco, with an age range of 25-51 years (adulthood and old age).